Silvicultural System for the Management of Silver Fir (Abies pindrow) Forests - Singh, R. V. (Indian Forester, 1976)
This paper discusses the implications involved in the change of silvicultural system from Selection System to Concentrated Regeneration Fellings amounting to almost clear felling under Uniform System for the management of silver fir forests. The silvicutural requirements of silver fir have been discussed and keeping the same in view the advantages and necessity of maintaining irregular stand structure are stressed. The experience of working some silver fir areas of Himachal Pradesh under Concentrated Regeneration Fellings suggests that such heavy fellings adversely affect the site and the establishment of silver fir plantations. From silvicultural stand-point the choice for a suitable silvicultural system for the management of silver fir forests may lie between Indian Irregular Shelterwood System, Group Selection System and Strip System depending upon the terrain, crop composition and other relevant factors. Present state of knowledge is not sufficient to categorically recommend a particular silvicultural system for the management of silver fir forests growing under different conditions and the need for extensive research to evolve a suitable silvicultural system for the management of these forests is stressed.